Reduced virulence of Serpulina hyodysenteriae hemolysin-negative mutants in pigs and their potential to protect pigs against challenge with a virulent strain. - Hyatt, D R (1994)
The role of the Serpulina hyodysenteriae hemolysin encoded by the tlyA gene in the pathogenesis of swine dysentery (SD) was studied. tlyA mutants of two S. hyodysenteriae strains (B204 and C5) were tested for virulence in pigs. None of the animals developed SD. However, after infection with wild-type strain B204 or C5, the incidence of SD was 100 or 60%, respectively. Thus, the tlyA-encoded hemolysin of S. hyodysenteriae is an important virulence factor in SD. The potential of these mutants to protect pigs against challenge with a virulent S. hyodysenteriae strain was also studied. After challenge with wild-type strain B204, 50% of pigs previously inoculated with the B204 tlyA mutant were protected, whereas all control pigs contracted SD. None of the pigs previously inoculated with the C5 tlyA mutant developed SD upon challenge with wild-type strain B204, whereas 40% of the control pigs developed SD in this experiment. Thus, previous colonization with S. hyodysenteriae tlyA mutants in pigs provides partial protection against challenge with a virulent S. hyodysenteriae strain.